A human rights-based approach to improve access to insulin and other aspects of diabetes care. (January 2022) - Brennan, Frank; Williams, Paul; Armstrong, Kate; Klatman, Emma; Donelan, Neil; Ogle, Graham D.; Eussen, Amy; Jenkins, Alicia J.
Abstract: Many nations struggle to provide adequate diabetes care. Legal as well as moral obligations may facilitate access. International human rights law places obligations on governments to ensure the accessibility and affordability of insulin (a World Health Organization essential medicine), and other components of diabetes care. Despite this obligation, the global reality is that access remains deficient. A human rights approach facilitating the improvement of diabetes services and equitable access to insulin provides a strong framework, theoretically and practically, for advocacy and policymaking changes. This approach links governments to their international obligations, fosters the ideal of, and adherence to, national essential medicine lists, complements the pursuit of international goals in non-communicable diseases, and should influence the actions of pharmaceutical and device companies. This approach empowers patients, families, and communities living with diabetes, and grounds actions by governments, clinicians, and non-government organisations in the principles of dignity, non-discrimination, and equity of access.